A Critical Appraisal of Using Digital Literacy as A Transformational Leadership Style in An Educational Context - Alhejaili, Anwar Safar (Journal of Educational and Psychological Sciences, 2022)
School leadership is only second to classroom instruction in terms of influence on student learning. The strengths of digital literacy lie in its ability to employ the transformational leadership approach to guide and direct the educational goals whereas its weakness rests on its susceptibility to failure to influence educational achievement as anticipated especially if it is wrongly implemented. With a particular focus on the Saudi Arabian educational context, the objective of this critical assessment in this area is to lay bare the benefits and shortcomings of adopting the digital literacy scheme so as to inspire change-oriented school leadership. The strengths identified include the capability to inspire and lead positive change within an educational setting, ensure a technology-oriented basis for organisational change, provide a platform for empowering a school community by inspiring genuine collaboration among the stakeholders, and to nurture all-round educational technology leaders. The analysis finds digital literacy as an approach to transformational leadership weak in that its effectiveness is dependent on the self-efficacy of the educational leader involved vis-à-vis their digital proficiency, the digital competence of the school as well as the access to the requisite professional and trade standards and their applicability. The critical appraisal offers a starting point upon which educational supervisors can effectively implement the digital literacy approach in their efforts to lead, direct and inform the desired transformation in an education setting.